2004
DOI: 10.1002/gcc.20118
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a rapamycin analog (CCI‐779) and IFN‐γ in tuberous sclerosis mouse models

Abstract: Tuberous sclerosis complex (TSC) is a familial tumor disorder for which there is no effective medical therapy. Disease-causing mutations in the TSC1 or TSC2 gene lead to increased mammalian target of rapamycin (mTOR) kinase activity in the conserved mTOR signaling pathway, which regulates nutrient uptake, cell growth, and protein translation. The normal function of TSC1 and TSC2 gene products is to form a complex that reduces mTOR kinase activity. Thus, mTOR kinase inhibition may be a useful targeted therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(138 citation statements)
references
References 38 publications
4
130
3
1
Order By: Relevance
“…However, in animal models and clinical trials, rapamycin, which is intended to block cell growth and proliferation, only partially inhibits tumor or disease progression (44,45), suggesting that alternative signaling mechanisms might be targeted. In fact, tuberous sclerosis complex 2-deficient tumors are particularly sensitive to the growth inhibitory effects of IFN-␥ and exhibit dysregulated STAT1 signaling (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, in animal models and clinical trials, rapamycin, which is intended to block cell growth and proliferation, only partially inhibits tumor or disease progression (44,45), suggesting that alternative signaling mechanisms might be targeted. In fact, tuberous sclerosis complex 2-deficient tumors are particularly sensitive to the growth inhibitory effects of IFN-␥ and exhibit dysregulated STAT1 signaling (46).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, rapamycin treatment reduced the tumor burden and increased survival in TSC-deficient animal models developing renal tumors (Kenerson et al, 2005;Lee et al, 2005Lee et al, , 2006Pollizzi et al, 2009;Woodrum et al, 2010).…”
Section: The Mtorc1 Inhibitors As Treatment For Tscmentioning
confidence: 99%
“…41,42 Given the considerable experience with rapamycin in human populations, translation of the pre-clinical findings to human clinical trials was rapid. Bissler et al 43 reported a singlesite, phase I/II open-label study of rapamycin for the treatment of renal AML in 25 patients with TSC or sporadic LAM.…”
Section: Treatment Of the Physical Features Of Tscmentioning
confidence: 99%